Thermo-hydro-mechanical simulation of cooling-induced fault reactivation in Dutch geothermal reservoirs - Bakul Mathur; Hannes Hofmann; Mauro Cacace; Gergő András Hutka; Arno Zang (Netherlands Journal of Geosciences, 2024)
Geothermal energy is one of the most viable sources of renewable heat. However, the potential risk of induced seismicity associated with geothermal operations may slow down the growth of the geothermal sector. Previous research has led to significant progress in understanding fluid-injection-induced seismicity in geothermal reservoirs. However, an in-depth assessment of thermal effects on the seismic risk was generally considered to be of secondary importance. This study aims to investigate the relative influence of temperature and key geological and operational parameters on the slip tendency of pre-existing faults. This is done through coupled thermo-hydro-mechanical simulations of the injection and production processes in synthetic geothermal reservoir models of the most utilized and potentially exploitable Dutch geothermal reservoir formations: Slochteren sandstone, Delft sandstone and Dinantian limestone.